2022
DOI: 10.3390/life12111845
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment Options for Epiglottic Collapse in Adult Obstructive Sleep Apnoea: A Systematic Review

Abstract: The critical role of epiglottis in airway narrowing contributing to obstructive sleep apnoea (OSA) and continuous positive airway pressure (CPAP) intolerance has recently been revealed. This systematic review was conducted to evaluate available surgical treatment options for epiglottic collapse in adult patients with OSA. The Pubmed and Scopus databases were searched for relevant articles up to and including March 2022 and sixteen studies were selected. Overall, six different surgical techniques were described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…A potential limitation of the study is that no distinction was made between secondary and isolated epiglottis collapse because we only measured the cross‐sectional area at both levels, retroglossal and retro‐epiglottic respectively. Epiglottis collapse may occur secondary to tongue base collapse, as an isolated AP inspiratory epiglottis collapse, or may co‐exist with obstruction at other sites, as described in a recent systematic review 50 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential limitation of the study is that no distinction was made between secondary and isolated epiglottis collapse because we only measured the cross‐sectional area at both levels, retroglossal and retro‐epiglottic respectively. Epiglottis collapse may occur secondary to tongue base collapse, as an isolated AP inspiratory epiglottis collapse, or may co‐exist with obstruction at other sites, as described in a recent systematic review 50 …”
Section: Discussionmentioning
confidence: 99%
“…Epiglottis collapse may occur secondary to tongue base collapse, as an isolated AP inspiratory epiglottis collapse, or may co-exist with obstruction at other sites, as described in a recent systematic review. 50 DISE was only performed in the supine position, which makes it more difficult to evaluate upper airway collapse before and after mandibular advancement in different sleeping positions. 51,52 However, because our study population was rather position-dependent, upper airway collapse was generally more pronounced in the supine position.…”
Section: Limitationsmentioning
confidence: 99%
“…Although various surgical approaches have been described for the management of pediatric EP, no study has demonstrated the superiority of 1 technique over the other 1‐6 . In the present study, we describe surgical outcomes in a cohort of patients undergoing a novel technique of TCE.…”
Section: Discussionmentioning
confidence: 94%
“…Primary EP can present as congenital or sleep or exercise‐induced laryngomalacia. Congenital laryngomalacia presents as stridor and respiratory distress while sleep and exercise‐induced EP occurs during sleep or during physical activity respectively and typically presents in older children (2‐18 years) 6 Secondary EP can be due to anterio‐posterior collapse of tongue base or lesions associated with tongue bases like lingual tonsillar hypertrophy, thyroglossal duct cysts, and vascular malformations. EP is also noticed in tracheostomized children and may prevent decannulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation